Urcování rozsahu onemocnení u non-Hodgkinových lymfomů--doporucení Kooperativní lymfomové skupiny - Sýkorová, A; Belada, D; Smolej, L; Pytlík, R; Benesová, K; Vásová, I; Papajík, T; Sálek, D; Procházka, V; Matuska, M; Brejcha, M; Kubácková, K; et al. (Klinicka onkologie, 2010)
BACKGROUNDS: The Ann Arbor system is typically used for the staging of Non-Hodgkin's lymphomas. This classification was nevertheless originally developed in the 1970s for Hodgkin's lymphoma, a disease usually confined to the lymph nodes with less frequent dissemination to extralymphatic organs/tissues and extremely rare primary extranodal involvement. Non-Hodgkin's lymphomas, however, are more often associated with extralymphatic involvement and primary extranodal lymphomas are relatively common (approximately 1/3 of cases). Therefore, the value of the Ann Arbor staging system appears to be limited in these cases. An analysis of data from centres participating within the Czech Lymphoma Study Group showed that staging of Non-Hodgkin's lymphomas with extranodal involvement is not uniform. DESIGN: At the end of 2009, a draft for a Non-Hodgkin's lymphomas staging system was put forward for use by the lymphoma register of the Czech Lymphoma Study Group with special regard paid to the involvement of extralymphatic organs/tissues. This draft was further refined following comments from members of the Czech Lymphoma Study Group committee and the final form was accepted at the meeting of the Czech Lymphoma Study Group committee in January 2010. RESULTS: A consensus was reached at the meeting of the Czech Lymphoma Study Group committee regarding the staging of various combinations of nodal and extranodal involvement. For the purpose of suitable staging and appropriate treatment intensity, extranodal organs were divided into "major"--liver, lungs, bones, mesothelium (pleura, peritoneum, pericardium) and soft tissues. All other organs were defined as "minor". CONCLUSION: The Ann Arbor staging system is suitable for the staging of Non-Hodgkin's lymphomas with lymph node/lymphatic tissue involvement. As regards the extralymphatic spread of the disease or primary extranodal lymphomas, this classification should rather be adapted to practical needs. The validity of the updated classification system will be assessed in both prospective and retrospective Czech Lymphoma Study Group studies.
Keywords: Neoplasm Staging; nehodgkinský lymfom; staging nádorů; Humans; lidé; Lymphoma, Non-Hodgkin